Quantifying the effects of temperature and salinity on partitioning of hydrophobic organic chemicals to silicone rubber passive samplers - Jonker, Michiel T O; van der Heijden, Stephan A; Kotte, Marcel; Smedes, Foppe (Environmental science & technology, 2015)
Nowadays, passive sampling is a widely applied technique to determine freely dissolved aqueous concentrations of hydrophobic organic chemicals (HOCs), such as polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs). Crucial to the measurements are sampler-water partition coefficients, which are generally determined in the laboratory under "standard conditions" (in freshwater at 20 °C). Theoretically, however, the coefficients are dependent on environmental conditions, such as temperature and salinity. Yet, there are insufficient experimental data in the scientific literature to prove this for different polymers. Several polymers are already being applied during field monitoring, however, and neglecting any effects may lead to imprecise results. In the present study, we therefore quantified the effects of temperature and salinity on the sampler-water partition coefficients of PAHs and PCBs for silicone rubber, a material used in Dutch passive sampling monitoring campaigns. The results demonstrated a chemical-specific and hydrophobicity-dependent temperature effect, being independent of salinity, and a chemical- and temperature-independent salinity effect. Based on the obtained data, location-specific silicone rubber-water partition coefficients (Ksr-w; adjusted for temperature and salinity) can be calculated. The impact of applying such location-specific values was demonstrated using the Dutch passive sampling field monitoring database, covering ten years of PAH and PCB data for several locations. Adjusting the Ksr-w values resulted in aqueous concentrations that were lowered by a factor of 1.6 on average. The reduction was rather constant because of the manner of sampling (under nonequilibrium conditions and using performance reference compounds) and calculating. When sampling under equilibrium conditions in seawater at temperatures at about freezing, and/or applying different calculation approaches, the adjustment effect can potentially increase up to a factor of about 5-6 for the more hydrophobic PAHs and PCBs. Although this study exclusively focused on silicone rubber, qualitatively the results will also apply to other passive sampling materials.
Keywords: polycyklické aromatické uhlovodíky; polychlorované bifenyly; salinita; referenční standardy; Temperature; Hydrophobic and Hydrophilic Interactions; Environmental Monitoring; teplota; Polycyclic Aromatic Hydrocarbons; Salinity; hydrofobní a hydrofilní interakce; časové faktory; Reference Standards; monitorování životního prostředí; organické látky; Organic Chemicals; Silicone Elastomers; silikonové elastomery; Time Factors; Polychlorinated Biphenyls